Multi-sensor magnetoencephalography with atomic magnetometers - Johnson, Cort N (2013)
The authors have detected magnetic fields from the human brain with two independent, simultaneously operating rubidium spin-exchange-relaxation-free magnetometers. Evoked responses from auditory stimulation were recorded from multiple subjects with two multi-channel magnetometers located on opposite sides of the head. Signal processing techniques enabled by multi-channel measurements were used to improve signal quality. This is the first demonstration of multi-sensor atomic magnetometer magnetoencephalography and provides a framework for developing a non-cryogenic, whole-head magnetoencephalography array for source localization.